A Programmatic Approach to Patient Blood Management – reducing transfusions and improving patient outcomes - Farmer, Shannon; Trentino, K.; Hofmann, Axel; Semmens, James; Mukhtar, Syed Aqif; Prosser, G.; Hamdorf, J.; Rao, S.; Leahy, M. (Bentham Science, 2015)
In July 2008, the Western Australia (WA) Department of Health embarked on a landmark 5-year project to implement a sustainable comprehensive health-system-wide Patient Blood Management Program. Fundamentally, it was a quality and safety initiative, which also had profound resource and economic implications. Unsustainable escalating direct and indirect costs of blood, potentially severe blood shortages due to changing population dynamics, donor deferrals, loss of altruism, wide variations in transfusion practice and growing knowledge of transfusion limitations and adverse outcomes necessitate a paradigm shift in the management of anemia and blood loss. The concept of patient-focused blood management is proving to be an effective force for change. This approach has now evolved to embrace comprehensive hospital-wide Patient Blood Management Programs. These programs show significant reductions in blood utilisation, reduced costs while achieving similar or improved patient outcomes. The WA Program is achieving these outcomes across a health jurisdiction in a sustained manner.